Can we be part of the pride? Reading animals through comics in the undergraduate classroom - Baraw, Charles; Smyth, Andrew (Animal comics: Multispecies storyworlds in graphic narratives, 2017)
Animal characters abound in graphic narratives ranging from Krazy Kat and Maus to WE3 and Terra Formars. Exploring these and other multispecies storyworlds presented in words and images, Animal Comics draws together work in comics studies, narrative theory, and cross-disciplinary research on animal environments and human-animal relationships to shed new light on comics and graphic novels in which animal agents play a significant role. At the same time, the volume's international team of contributors show how the distinctive structures and affordances of graphic narratives foreground key questions about trans-species entanglements in a more-than-human world. The writers/artists covered in the book include: Nick Abadzis, Adolpho Avril, Jeffrey Brown, Sue Coe, Matt Dembicki, Olivier Deprez, J. J. Grandville, George Herriman, Adam Hines, William Hogarth, Grant Morrison, Osamu Tezuka, Frank Quitely, Yu Sasuga, Charles M. Schultz, Art Spiegelman, Fiona Staples, Ken'ichi Tachibana, Brian K. Vaughan, and others.
Google-Books-ID: 8rU7DwAAQBAJ
Keywords: Art / Subjects & Themes / Landscapes & Seascapes; Comics & Graphic Novels / Literary; Humor / Form / Comic Strips & Cartoons; Literary Criticism / Comics & Graphic Novels; dept.eng

War in Travel Literature - Dubino, Jeanne; Kocabıyık, Orkun; Marino, Elisabetta; Smyth, Andrew J. (Cambridge Scholars Publishing, 2023)
These twelve chapters show how war functions as a subject, theme, impetus–willing and not–and backdrop in travel writing. Literature about travel and war in tandem enables readers to rethink both categories. The forms of travel writing about war addressed in this collection, including cookbooks and military magazines along with nonfiction narrative and memoir, reveal how heterogenous travel writing can be. To study travel in connection with war expands readers' understanding of the multiple motivations instigating travellers' journeys. War is about more than fighting on a battlefield; its reach is extensive, encompassing the spheres surrounding its battlefields and fronts. The many actors involved in any conflict attests to the ways war is absorbed into their worlds, permeates their thoughts and spurs their actions. Readers interested in travel literature from the beginning of the nineteenth century through the present day will find this volume to be of especial interest.
Google-Books-ID: uYLxzwEACAAJ
Keywords: dept.eng